Molecular and Cellular Mechanisms of Metformin in Cervical Cancer - Chen, Ya-Hui (Cancers (Basel), 2021)
SIMPLE SUMMARY: The potential effects of metformin in terms of cancer prevention and therapy have been widely studied, and a number of studies have indicated its potential role in cancer treatment. Metformin exerts anticancer effects, alone or in combination with other agents, on cervical cancer in vitro and in vivo. Metformin might thus serve as an adjunct therapeutic agent for cervical cancer. ABSTRACT: Cervical cancer is one of the major gynecologic malignancies worldwide. Treatment options include chemotherapy, surgical resection, radiotherapy, or a combination of these treatments; however, relapse and recurrence may occur, and the outcome may not be favorable. Metformin is an established, safe, well-tolerated drug used in the treatment of type 2 diabetes; it can be safely combined with other antidiabetic agents. Diabetes, possibly associated with an increased site-specific cancer risk, may relate to the progression or initiation of specific types of cancer. The potential effects of metformin in terms of cancer prevention and therapy have been widely studied, and a number of studies have indicated its potential role in cancer treatment. The most frequently proposed mechanism underlying the diabetes–cancer association is insulin resistance, which leads to secondary hyperinsulinemia; furthermore, insulin may exert mitogenic effects through the insulin-like growth factor 1 (IGF-1) receptor, and hyperglycemia may worsen carcinogenesis through the induction of oxidative stress. Evidence has suggested clinical benefits of metformin in the treatment of gynecologic cancers. Combining current anticancer drugs with metformin may increase their efficacy and diminish adverse drug reactions. Accumulating evidence is indicating that metformin exerts anticancer effects alone or in combination with other agents in cervical cancer in vitro and in vivo. Metformin might thus serve as an adjunct therapeutic agent for cervical cancer. Here, we reviewed the potential anticancer effects of metformin against cervical cancer and discussed possible underlying mechanisms.